(untitled) (European Journal of Behavioral Sciences, 2020)
The article reveals the specifics of Russian national culture and its role in business. The data of studies of Russians are summarized in behavioral context. The historical periods of Russia’s development and governance and their influence on behavior are described in the business environment. The greatest differences are noted between the Russian and Anglo-Saxon mentality. Russians are described in typical situations at the present stage of Russian economy development - the formal use of IT, bureaucracy, subordination, the importance of personal contacts, and desire to control workers behavior during off-hours.